Company's Efficiency From a Strategic Perspective - Urbanowska-Sojkin, Elżbieta (Studia Oeconomica Posnaniensia, 2019)
Following the changes in the operating conditions of business entities, the problem of evaluating a company's achievements from a strategic perspective arises. The economic measures commonly used so far, do not meet the requirement of a comprehensive analysis and evaluation of the results of a company's activity from this perspective. The article analyses the nature of a company and the environment in which it operates, which allows one to specify the limitations and applicability of the term "efficiency" with reference to the evaluation of the company from a strategic perspective. The aim of the study is to assess the usefulness of the term "efficiency" for the evaluation of the company's development potential. The study was based on literature research, which currently enables the conceptualisation of efficiency dimensions, areas of analysis and evaluation of the enterprise, and types of efficiency in the strategic perspective.